The Development of Canva-Based Learning Media in Islamic Religious Education (PAI) for 7th Grade at MTs. Muhammadiyah Curup - Reni Dianti Rukmini; Wiwik Damayanti; Aida Rahmi Nasution; Epa Kristanti (The Future of Education Journal, 2024)
Religious education plays an essential role in shaping students' personalities and their devotion to worship. Achievement in Islamic Religious Education is influenced by both internal and external factors. Internal factors can be enhanced through support from parents and teachers, while external factors depend on the student's social environment. With the advancement of information and communication technology, the teaching and learning process has undergone a significant transformation. Creative educators utilize learning media to make lessons more engaging and tailored to students' characteristics. The purpose of this study is to develop effective and practical learning media that can enhance student interest in learning, foster good character, and meet the interactive learning needs of the digital era. This research employs a qualitative method with a descriptive approach. The findings suggest that Canva-based learning media, as a development product for Islamic Religious Education (PAI) lessons for 7th-grade students at MTs. Muhammadiyah Curup, can be used by adhering to the steps and guidelines of the development model and the available Canva application, enabling teachers to conduct lessons in an easy, quick, accurate, and effective manner.